2019
DOI: 10.1017/s1742058x19000237
|View full text |Cite
|
Sign up to set email alerts
|

Race, Nativity, and Multicultural Exclusion

Abstract: This article examines the exclusion of Afro-Mauritians (or Creoles) in Mauritian multiculturalism. Although Creoles represent nearly thirty percent of the population, they are the only major group not officially recognized in the Mauritian Constitution (unlike Hindus, Muslims, and the Chinese) and they experience uniquely high levels of socioeconomic and political marginalization despite the country’s decades-long policy of official multiculturalism. While scholarship on multiculturalism and nation-building in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Historically, individuals with African ethnicity have had a lower level of education compared with other ethnic groups in Mauritius. 26 In this study, we used the educational level as a proxy for socioeconomic status (SES). Previous studies have shown increased morbidity and mortality in individuals with lower SES compared with those with higher SES, and the individuals with lower SES were more likely to be hypertensive and had higher psychological stress, which could contribute to the development of LVH.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, individuals with African ethnicity have had a lower level of education compared with other ethnic groups in Mauritius. 26 In this study, we used the educational level as a proxy for socioeconomic status (SES). Previous studies have shown increased morbidity and mortality in individuals with lower SES compared with those with higher SES, and the individuals with lower SES were more likely to be hypertensive and had higher psychological stress, which could contribute to the development of LVH.…”
Section: Discussionmentioning
confidence: 99%